Penegakan Hukum terhadap Penyalahgunaan Nitraous Oxide - Lutfia Alydia (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Nitrous oxide is a medical gas increasingly misused for recreational purposes in Indonesia. Its distribution through social media and online marketplaces has facilitated public access outside medical channels. This study applies an empirical qualitative legal method through interviews with users, the National Narcotics Agency and medical professionals. The findings reveal significant health and social impacts of nitrous oxide abuse, while legal regulation remains administrative without clear criminal sanctions. This situation creates a legal vacuum that weakens law enforcement effectiveness.